A hybrid damage assessment and recovery approach in multilevel databases. (c2018) - Zarif, Omar B. El (2018)
In the midst of the technology advancements that we are witnessing nowadays, information security is of an essence. Information warfare is actively introducing new offensive strategies to exploit databases that include sensitive data, or even classified and secret data in the case of the multilevel ones. The attacks vary from stealing sensitive data, to modifying crucial records, or simply corrupting the database. Many approaches to detect and prevent from such attacks are available, from firewalls to intrusion detection systems. But in many cases, prevention can fail, and detection could happen long after the attack. That implies the necessity of damage assessment and recovery to restore the database integrity. We introduce in this work a hybrid lightweight approach based on clustering and graphs to track transactional dependencies in multilevel databases. To the best of our knowledge, targeting multilevel databases has not been tackled before, so we will compare our approach with single level databases approaches, taking into consideration the additional security and integrity constraints imposed by the multilevel nature.